2014
DOI: 10.2514/1.a32789
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Attribute Tradespace Exploration for Survivability

Abstract: Multi-Attribute Tradespace Exploration for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Wade et al. () found that only two of the reviewed papers, Ross, Stein, and Hastings () and Sitterle, Freeman, Goerger, and Ender (), considered a large number of alternatives, multiple system performance measures, the use of modeling and simulation techniques, and affordability analysis to compare cost versus value. Ross et al.…”
Section: Engineering Resilience Quantification Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Wade et al. () found that only two of the reviewed papers, Ross, Stein, and Hastings () and Sitterle, Freeman, Goerger, and Ender (), considered a large number of alternatives, multiple system performance measures, the use of modeling and simulation techniques, and affordability analysis to compare cost versus value. Ross et al.…”
Section: Engineering Resilience Quantification Literaturementioning
confidence: 99%
“…Ross et al. () described resilience as one of the three types of survivability and developed an eight‐phase methodology. They also suggested that “[s]urvivability may be incorporated more effectively at the architecture level rather than as an additive feature to a baseline system concept” and a tradespace analysis comparing cost, utility, and survivability may be useful to analyze alternatives.…”
Section: Engineering Resilience Quantification Literaturementioning
confidence: 99%
“…The Integrated Trade-Off Analysis Framework provides a means to perform a tradespace exploration. This framework can use single objective (also called attribute) or multiple objective tradespace exploration (also known as multi-attribute tradespace exploration-MATE [14]).…”
Section: Tradespace Explorationmentioning
confidence: 99%
“…It has been used as a standard technique in several applications in research and real-world problems, such as the airline industry [114], nuclear energy [115], earthquake projects [116] and farming systems [117]. MAUT has been incorporated in the multi-attribute trade-space exploration (MATE) paradigm for generating a multitude of system designs and identifying the optimal ones, [118], [119], [120] and [121]. It was also applied in establishing the requirements' specification of commercial aircraft [122], in evaluating space system designs for the telecommunications and deep-space observation missions [103], and the development of satellite value models [123].…”
Section: Multi-attribute Utility Theorymentioning
confidence: 99%